FTTH Unbundling: The Spanish Regulation in Retrospect - Zoraida Frias; Jorge Pérez Martínez (International Telecommunications Society (ITS), 2016)
This paper explores the effects of Virtual Unbundled Local Access (VULA) –or its absence- on the deployment of Fibre-To-The-Home (FTTH) networks in Spain in a retrospective way. First, we assess the impact of former wholesale broadband markets' regulation on FTTH investment and on the market structure evolution. Further on, based on coverage data from 2013, we provide an assessment of how would have NGA coverage looked like if the recently approved regulation for FTTH unbundling would have come into force in 2013 instead. We conclude that if a VULA had been available earlier, the amount of households with no access to any NGA infrastructure would have been up to 50% higher than it actually is. In return, full NGA facility-based competition would have been reinforced.
Keywords: 330; FTTH; New Generation Access; local loop unbundling; VULA